Use of the Marbel Wudu Application Learning Media to Increase Interest in Learning Islamic Religious Education at Al-Insan Pinrang Elementary School - Rizqi Fatimalasari; Sitti Jamilah Amin; Firman; Marhani; Kaharuddin (Universitas Muhammadiyah Palu, 2024)
This thesis discusses the use of learning media in enhancing students' interest in Islamic Education among fourth-grade students at SDIT Al-Insan Pinrang. The research aims to determine whether the use of the Marbel Wudu learning application can improve the interest in learning Islamic Education among fourth-grade students at SDIT Al-Insan Pinrang. The method employed is Classroom Action Research (CAR) using the spiral/cycle model by Kemmis and Taggart, consisting of two cycles with four stages in each cycle: planning, action implementation, observation, and reflection. The research subjects are 27 students. Data collection techniques include observation, questionnaires, and documentation. Teacher activity data is obtained through observation and analyzed to compare the activity levels in each cycle. Data on students' interest in learning are obtained through questionnaire distribution, which is then analyzed to observe improvements in each cycle. The research results indicate an increase in students' interest in the Islamic Education subject through the use of the Marbel Wudu learning application. This is proven by the increased effectiveness of the teaching methods implemented by the teacher. Based on the observation results in cycles I and II, in cycle I, the use of the Marbel Wudu learning application in Islamic Education learning obtained a percentage of 61.15% (fair), and in cycle II, the percentage increased to 81.92% (very good). Furthermore, the improvement in students' interest is reflected in the average increase in each cycle, with a classical percentage of 72.03% (good) in cycle I and 81.14% (very good) in cycle II, resulting in an improvement of 9.11%. This indicates that the use of the Marbel Wudu learning application can enhance students' interest in learning.